An Efficient Energy Consumption Technique in Integrated WSN-IoT Environment Operations - Thangarasu, G. (Institute of Electrical and Electronics Engineers Inc., 2019)
The data exchange volume in Wireless Sensor Networks (WSN) is increasing in recent years due to expansion of the WSN with Internet of Things (IoT). The wireless sensor networks act as a digital skin by providing information from a virtual layer, which can be accessed through any computational system. The availability of imbalanced resources and heterogeneous IoT communication leads to energy consumption constraints. This study proposed a method uses a Chaotic Whale Optimization framework to improve the consumption of energy in integrated WSN-IoT environment operations. The obtained energy optimization results compared with the other conventional methods. The result shows that proposed method obtains improved energy efficiency in integrated WSN-IoT environment. Â© 2019 IEEE.